EFFECT OF IRRIGATION METHODS ON WATER CONTENT DISTRIBUTION, WATER AND CORN PRODUCTIVITY - Masood, T. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Field experiment was carried out during spring seasons of 2015 in AL-Rasheed township southern of Baghdad, Iraq to study the effects of irrigation methods on water content distribution, water use efficiency and yield of corn. Four surface irrigation treatments were used: 100% conventional basin (control), 70% of control treatment basin irrigation, Conventional furrow and shallow furrow. Water content distribution results showed that shallow furrow irrigation decreased moisture content to 14.7, 18.3 % for 0-10 and 10-20 cm depth respectively, compared to conventional basin irrigation. The result showed that treatments of conventional furrow, shallow furrow and 70% basin irrigation reduced the depth of added water in rate of 33, 28 and 30%, respectively comperd to control treatment (884mm season-1). Conventional furrow irrigation significantly increased corn grain yield to all treatments except conventional basin. In the mean while, other treatment did not differ from the conventional irrigation method. Water use efficiency of conventional furrow irrigation was significantly higher than all other treatments with 80% increment than others. Thus the 70% basin irrigation and shallow furrow irrigation is more productive yield when compared with traditional irrigation.